2012
DOI: 10.5539/jas.v4n2p245
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Photosynthetic Metabolism and N2 Fixation at the Flowering Stage in Three Genotypes of Cowpea [Vigna unguiculata (L.) Walp.]

Abstract: Biological nitrogen fixation (BNF) in cultivars of cowpea is not yet understood. The hypothesis proposed by this study is that lack of basic technology, including sufficient mineral nutrition, combined with periods of water shortage during the crop cycle leads to insufficient photosynthetic metabolism in the flowering stage in nodulated plants. Two experiments were conducted in northeastern Brazil, one under field conditions and another in a greenhouse at near optimal conditions. Two of the principal cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…According to the authors, rhizobial symbiosis stimulated photosynthesis due to the removal of photosynthates sink limitation by the nodule activity. Oliveira et al (2012) also observed the same results to cowpea, where plants inoculated with a commercial rhizobia strain showed more efficiency on gas exchanges than the control plants. Also, in the present study, peanut presented a better gas exchange behavior when inoculated with SEMIA 6144.…”
Section: Nodulation and Agronomical Traitssupporting
confidence: 70%
“…According to the authors, rhizobial symbiosis stimulated photosynthesis due to the removal of photosynthates sink limitation by the nodule activity. Oliveira et al (2012) also observed the same results to cowpea, where plants inoculated with a commercial rhizobia strain showed more efficiency on gas exchanges than the control plants. Also, in the present study, peanut presented a better gas exchange behavior when inoculated with SEMIA 6144.…”
Section: Nodulation and Agronomical Traitssupporting
confidence: 70%
“…One potential strategy to reduce the effects of abiotic stress in peanuts is the biological interaction with rhizobia strains. This interaction may result in the selection of promising macro and micro-symbiont associations, as already shown for cowpea (Oliveira et al 2012) and common beans (Suárez et al 2008).…”
Section: Introductionmentioning
confidence: 67%
“…Higher N content in plants with full water supply, compared to those subjected to water deficit, indicated that in the period of low water availability, the activity of the nodules on nitrogen fixation was reduced or completely stopped. But the inoculation of rhizobia results in other benefits for the hosts, besides the N fixation (Suárez et al 2008;Oliveira et al 2012). These positive effects were observed in the physiological traits evaluated in the present study, indicating that the inoculation of ESA 123 and SEMIA 6144 can benefit the peanuts by other plant growth promoting mechanisms, in addition to BNF, what is important to strain selection for drylands, as the Brazilian semi-arid region.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rhizobia, bacteria that induce the development of root and/or stem nodules in legumes, has been an alternative to optimize agricultural production through a reduced need for nitrogen fertilizers. In addition to nitrogen fixation, the rhizobium-legume interaction may contribute to host resistance to abiotic stresses such as drought, as has been demonstrated for tropical legumes such as cowpea (Oliveira et al, 2012) and peanut (Melo et al, 2016;Barbosa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%